2000
DOI: 10.1046/j.1440-1622.2000.01801.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of the axilla in early breast cancer: is it time to change tack?

Abstract: The standard surgical treatment of the axilla in patients with early breast cancer is about to undergo a radical change. Although axillary dissection is an excellent procedure for both staging and local control, particularly in the clinically positive axilla, it has considerable morbidity and may understage a significant proportion of patients, because it will usually miss micrometastases that can occur in approximately 10% of 'node negative' patients. An increasing number of patients whose tumours are either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…Unfortunately, AC is associated with significant morbidity, including arm stiffness, arm swelling and increased risk of infection. While different series have reported various incidences of permanent problems, a clinically relevant rate of 10% is generally accepted 1,3,7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, AC is associated with significant morbidity, including arm stiffness, arm swelling and increased risk of infection. While different series have reported various incidences of permanent problems, a clinically relevant rate of 10% is generally accepted 1,3,7 …”
Section: Introductionmentioning
confidence: 99%
“…The presence and extent of axillary metastatic disease is the most sensitive prognostic factor for breast cancer 1–3 . A study of over 20 000 patients showed that the 5‐year survival for a patient with breast cancer less than 2 cm in size is 98% in the absence of node involvement and 80% if metastases are found 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Dissection of the node can be at times, technically more difficult since the position of the sentinel node is not always predictable. This could lead to creation of tissue flaps and risk of infection or necrosis (64). The node or nodes hence defined by the blue dye is then excised and evaluated by histopathology.…”
Section: The Dyementioning
confidence: 99%